Pengaruh Tingkat Perputaran Modal Kerja Truktur Modal dan Ukuran Perusahaan, terhadap Profitabilitas Pada Perusahaan Whole Sale and Retail Trade di Bursa Efek Indonesia Periode 2008-2011 - Titin Waseri; Kirmizi '; Al-azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aimed to significantly influence the working capital turnover, debt to equity ratio (DER) and firm size affect the profitability of whole sale and retail trade companies are listed at Indonesia Stock Exchange for period from 2008 until 2011. The Model which used in this research is multiple linear regression. Data was obtain from 23 whole sale and retail trade companies as the sample in research in Indonesian Stock Exchange during the period of 4 years in a row. The data is processed by using SPSS for windows version 17. The results of this research can be concluded that the working capital turnover and firm size have a significant effect on profitability. While invendebt to equity ratio (DER) no effect on profitability. The result of simultant test, working capital turnover, debt to equity ratio (DER) and firm size have significantly influence profitability.Keywords : Working Capital Turnover, Debt to Equity Ratio (DER), Firm Size, Profitability